Macrosystematics of Didymodon sensu lato (Pottiaceae, Bryophyta) using an analytic key and information theory - Zander, R.H. (Український ботанічний журнал, 2016)
Evolutionary trees (caulograms) and phylogenetic cladograms for both morphological and molecular analyses of certain species in the moss genus Didymodon (Pottiaceae, Bryophyta) were compared. A new two-step macrosystematic (macroevolutionary systematics) method of calculating statistical support for both linear order and lineage direction of evolution is introduced. This involves clustering of taxa in sets by minimization of redundancy using cladograms and minimum parsimony, then building an often-branched linear model by maximization of information on gradual evolution by ordering species through adding informational bits for advanced traits and subtracting them for reversals. Cladistic analysis is considered to be similar to cryptographic code-breaking, with that code key then used for modelbuilding following theory. Very high Bayesian support was computed for lineages in the morphological analyses, which stand up well to high support for past molecular studies. The caulogram allowed for predictions not possible with cladograms. The importance of using information on both shared and serial descent is discussed.